A stag beetle knife can achieve stabler and safer endoscopic submucosal dissection in the esophagus - Funasaka, Kohei; Horiguchi, Noriyuki; Yamada, Hyuga; Koyama, Keishi; Tahara, Tomomitsu; Nagasaka, Mitsuo; Nakagawa, Yoshihito; Ohno, Eizaburo; Kuzuya, Teiiji; Miyahara, Ryoji; Shibata, Tomoyuki; Hirooka, Yoshiki (Endoscopy International Open, 2023)
Background and study aims Esophageal endoscopic submucosal dissection (ESD) has a higher complication rate than gastric ESD. Scissor-type devices, including the stag beetle (SB) knife, are reportedly safer and have shorter procedure times than tip devices. To clarify the characteristics of the SB knife, we compared the treatment outcomes of esophageal ESD with a tip-type knife to those with an SB knife combination.Patients and methods Between January 2016 and March 2023, clinical data from 197 lesions in 178 patients who underwent esophageal ESD were analyzed retrospectively. Every lesion was assigned to either the tip-type group or the SB group based on the devices with which the submucosa was initially dissected. We compared procedure time and complications and analyzed the risk of muscular exposure using multivariate analysis.Results Procedure time was not significantly different between the tip-type and SB groups (60.3±42.2 min vs. 58.8±29.1 min). The variation in procedure time was significant according to F test P=0.002). Incidence of muscular exposure was significantly lower in the SB group than in the tip-type group (24.5% vs. 11.1%, P=0.016). These differences were significant in resected specimens larger than 21 mm. Procedure time over 60 minutes (odds ratio [OR] 2.5, 95% confidence interval [CI]: 1.15–5.42, P=0.02) was a risk factor for muscular exposure, and submucosal dissection with an SB knife was a safety factor (OR 0.4, 95% CI: 0.18–0.89, P=0.02).Conclusions Performing esophageal ESD with an SB knife is a safe procedure with less variation in procedure time and less muscule exposure.
Keywords: Quality and logistical aspects; Performance and complications